UPAYA MENGHADIRKAN LARAS SALENDRO DALAM SOUNDSCAPE KEHIDUPAN SEHARI-HARI GUNA MENUNJANG MATA KULIAH SISTEM NOTASI DI PRODI KARAWITAN - Zakaria S, Mustika Iman (Paraguna, 2018)
The  environment  is one  aspect  that  supports the  realization   of a  good  learning process.  In  the process of learning  Sundanese  musical art,  one  of the  materials taught  in the process was  the  mastery of certain sounds or sounds that  certainly require auditive  sensitivity.  scale  of salendro  as  one of the  materials that  must be mastered by  students becomes  one  of the  sounds that  are  actually   extraneous to the ears  of student's soundscape.  This caused the slow  acceleration  of the mastery of the sound.  Through efforts to condition  certain environments in the context  of the learning process,  it becomes  one of the choices that must be made  especially by the students  themselves.  Sound   environment  or soundscape  becomes   an  important issue  that  the  writer  adopts,  through  literature  studies  and  descriptive  analysis  in the  context   of presenting  the  Salendro   scale   tone  in  the  daily   environment  of students  in  order  to  enrich  the   auditive  experience  in  order   to  accelerate   the mastery acceleration  of the sound  of the salendro  scale.